The impact of sleep quality and duration on leptin, appetite, and obesity indices in adults (Faculty of Medicine Universitas Indonesia, 2020)
BACKGROUND Poor sleep duration and quality were previously reported to increase the risk of obesity. This study was aimed to evaluate the impact of sleep quality and duration on leptin, appetite, and adiposity in Indonesian adults. METHODS This cross-sectional study recruited adults in Yogyakarta, Indonesia, in 2016. Sleep quality was assessed using the Pittsburgh sleep quality index, appetite was evaluated using the community nutrition appetite questionnaire, and dietary intake was assessed by interviews using the semi-quantitative food frequency questionnaire. Sleep duration was also asked. Obesity indices were measured using the body mass index (BMI), waist-hip circumference, and percentage of body fat. Leptin was analyzed using the enzyme-linked immunosorbent assay. A Spearman analysis was done to evaluate the correlation between sleep quality, sleep duration, anthropometric measures, dietary intake, appetite, and leptin. RESULTS 244 adults participated in this study. This study showed that lower sleep quality and duration was significantly correlated with higher body weight (r = 0.129, p = 0.043 and r = −0.228, p<0.001), BMI (r = 0.176, p = 0.006 and r = −0.202, p = 0.001), and waist circumference (r = 0.179, p = 0.005 and r = −0.254, p<0.001). There was a correlation between poor sleep quality and higher leptin concentration (r = 0.186, p = 0.004). Sleep quality and duration were not associated with appetite (r = 0.109, p = 0.109 and r = −0.043, p = 0.500). CONCLUSIONS This study found that lower sleep quality was correlated with higher BMI, higher leptin concentration, but not appetite.